Isolation and selection of Bacillus cereus specific phages from hospital wastewater - Anwar Rovik; SAEFUDDIN ‘AZIZ; HENDRO PRAMONO (Society for Indonesian Biodiversity, 2020)
Abstract. Rovik A, ‘Aziz S, Pramono H. 2020. Isolation and selection of Bacillus cereus specific phages from hospital wastewater. Biodiversitas 21: 2871-2877. Bacillus cereus (B. cereus) is a pathogenic bacterium that frequently contaminates food by producing entero and emetic toxins. B. cereus has shown resistance to various antibiotics, especially ?-lactam antibiotics. An alternative to control B. cereus contamination is the use of bacteriophages. This study aimed to isolate and screen B. cereus specific phages from hospital wastewater in Banyumas District. The research was conducted descriptively through isolation, purification, titer determination, host ranges, and adsorption rate determination. A total of 29 isolates of B. cereus-phages were isolated from hospital wastewater in Banyumas with various titers, ranged from 0.14-3.76 x 107 PFU.mL-1. Isolated phages could be grouped into two, narrow host range (14 phages) and broad activity spectra (15 phages) that infect both Gram-positive and negative bacteria i.e. B. subtilis, B. fragilis, B. licheniformis, Citrobacter freundii, Klebsiella pneumoniae, Salmonella thypi, and Escherichia coli. The infections had a latency period of 60-120 minutes. The decrease of culture absorbance value ranged from 0.06 to 0.41, while the control tended to increase by 0.39. The largest decreases were showed by phage isolates RSBMS-2 and RSBMT-1 with 0.41 and 0.37, respectively.